Effect of injection timing and duration on the performance of diesel engine fueled with port injection of oxygenated fuels. Issue 6 (3rd June 2023) - Ranganatha Swamy, L.; Banapurmath, N. R.; Chandrashekar, T. K.; Soudagar, Manzoore Elahi M.; Gul, M.; Nik-Ghazali, Nik-Nazri; Mujtaba, M. A; Shahapurkar, Kiran; Ağbulut, Ümit; Alshehri, Hashim M.; Sajjan, A.M.; Goodarzi, Marjan
Abstract: An alarming adulteration of nature with automotive tail pipe emissions causing global warming demands suitable engine modification. Further use of alternative renewable fuels with fine-tuning the engine and required modifications could reduce the diesel engine emissions. Oxygenated fuels (such as methanol, ethanol and Butanol) act as stand-in fuel that could enrich the global energy requisites and affirmatively downsize the emissions by accelerating combustion efficiency. Under this circumstance, the experimental analysis was done on a single-cylinder four-stroke DI CI engine using conventional diesel as fuel by injection of ethanol, diethyl ether (DEE) and Butanol independently to into intake manifold at three injection timings viz., TDC, 5°ATDC and 10°ATDC respectively under the constant 27°CA injection duration with the help of a distinct setup comprises of the electronic control unit (ECU) and injector system. The resolutions drawn from the recorded results at 80% load during experimentation summarized that DEE exhibited improved BTE of 2.5% and 1% and reduced smoke emissions of 12.54% and 10.6% compared to that obtained with ethanol and Butanol, respectively. On the other hand, DEE emitted excessive NOx and inferior HC, CO emissions compared to ethanol and Butanol apart from shortened ignition delay and combustion duration. The conclusions are drawn from the injection of oxygenates that apart from the perspective of performance, DEE injection at the 5°ATDC was noticed to be optimal at 27°CA injection duration (3 ms) too for emissions characteristics of a diesel engine.